FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA PENDIDIKAN ANAK DI KENAGARIAN UJUNG GADING KECAMATAN LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Atmi, Zul; Dasrizal, Dasrizal; Iswandi U, Iswandi U (Pendidikan Geografi, 2013)
This study aimed to obtain information, analyze and discuss data on factors affecting the education of children in the low end Kenagarian Ujung Gading Lembah Melintang Pasaman Barat. This type of research was descriptive correlational. The study population is families who settled in the Kenagarian Ujung Gading Lembah Melintang Pasaman Barat with a population of 9,503 households. The samples were taken in two ways, the sample areas were taken by purposive sampling technique that is most widely children who do not continue the Jorong Taluk Ambun and Jorong Irian. Respondent sample taken with proportional random sampling technique by 10% so that the total sample of 113 households. The results: (1) There is no education there is the influence of parents on childrens education due to the low count Ï2 <Ï2 table (11.693 <21.026), (2) There is no influence of parental income on childrens education in the low end Kenagarian Ujung Gading Lembah Melintang Pasaman Barat count as Ï2 <Ï2 table (2.772 <9.488), and (3) There is no effect of family size on childrens education in the low end Kenagarian Ujung Gading Lembah Melintang Pasaman Barat count as Ï2 <Ï2 table. (13.389 <21.026)Â